Analysis Of The Relationship Volume Density And Traffic Speed On Street Sruni Buduran Sidoarjo With Greenshields Method - Apteda, Prastama Errian; Zainab, Siti (Journal of Management Economic and Financial, 2023)
Sidoarjo Regency has several road sections that often have traffic problems such as congestion. The congestion is caused by economic improvement which also causes a person's mobility to increase so that there is a fairly high traffic movement. Likewise, what happened to the Sruni Buduran Highway, Tebel Buduran Highway, and Buduran Sidoarjo Highway East Java as study areas. By reaching a road length of 3 Km. The study in this study aims to analyze and map the mathematical relationship of Volume - Density - Traffic Speed, so that the value of free flow speed, maximum density, and maximum volume can be obtained on the Sruni Buduran Sidoarjo road section. With the method used is the Greenshields model, which is then compared with capacity using the Indonesian Road Capacity Guidelines method (2014), the survey was conducted at 08.00 – 18.00, with 4 survey days, Monday to Thursday in each segment to obtain primary data in calculating the Greenshields mathematical model. From this study, it shows that the highest free flow speed (Sff) value occurred on Wednesday, May 17, 2023 on segment 3 of the Buduran Sidoarjo Highway, (Sidoarjo - Surabaya) with a value of Sff = 70.888 km / hour, the highest capacity or maximum current (VM) occurred on Tuesday, May 2, 2023 on segment 1 of the Sruni Buduran Highway, (Surabaya - Sidoarjo) VM = 722.005 emp/hour,  the highest speed in maximum traffic flow (SM) conditions occurred on Wednesday, May 17, 2023 on segment 3 of the Buduran Sidoarjo Highway, (Sidoarjo - Surabaya) SM = 37.444 km / hour, and the highest density in maximum traffic flow (DM) conditions occurred on Tuesday, May 2, 2023 on segment 1 of the Sruni Buduran Highway, (Surabaya - Sidoarjo) DM = 22.549 emp/km.